MEDIA PEMBELAJARAN MATEMATIKA SD (PENGEMBANGAN KEGIATAN BELAJAR MATEMATIKA DENGAN MEDIA/ ALAT PERAGA) - Rosmanila Lubis; Ahmad Jarnawi Lubis; Hotnida; Almira Almir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Mathematics in elementary schools requires an innovative approach to improve students' conceptual understanding and learning interest. This study aims to develop and analyze the effectiveness of using learning media or teaching aids in mathematics learning activities in elementary schools. The research method used is research and development (R&D) with qualitative and quantitative approaches. Data were collected through observation, interviews, and student learning outcome tests. The study results indicate that using appropriate learning media can increase student engagement, clarify abstract concepts, and improve mathematics learning outcomes. These findings suggest that the development of interactive and contextual learning media is essential to support a more effective learning process. Keywords: learning media, teaching aids, elementary school mathematics, development, learning outcomes